The implementation of feedback to facilitate students’ self-regulation in learning English in Madrasah Aliyah context - Nurul Alfiah Wahyuni; Aminah Suriaman; Sriati Usman; Darmawan Darmawan; Mochtar Marhum; Anjar Kusuma Dewi; Jeric Romero (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
Feedback is necessary to measure whether students have understood well the lesson that has been delivered. Students should be given feedback to help them become autonomous learners who can regulate aspects of their thinking, motivation, and behaviour during learning. The study aimed to find out how feedback is implemented by the teacher based on Nicol’s framework and to find out students’ perceptions towards the application of formative assessment. A questionnaire was administered to get the data on how feedback that facilitates students’ self-regulation is implemented at MA Negeri 2 Kota Palu. Further, an in-depth interview was used to get students’ perception towards the implementation of feedback. The questionnaire showed that the implementation of feedback at MA Negeri 2 Kota Palu helps clarify what good performance is, facilitates the development of self-assessment in learning, delivers high quality information to students about their learning, encourages teacher and peer dialogue around learning, encourages positive motivational beliefs and self-esteem, and provides opportunities to close the gap between current and desired performance. The interview revealed that students have positive perception towards the feedback implemented by the teacher.